2022
DOI: 10.3390/su141912590
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Design Strategy of Rehabilitation Space for Patients with Cognitive Disorders Based on the Environmental Adaptation of Disease Symptoms

Abstract: Under the dual pressure of the large number of patients and the funding of expensive treatments, the established medical model is no longer able to meet the treatment needs of patients with cognitive disorders. Cognitive disorders cannot be cured, and the proposed MCI stage provides a window of opportunity for early intervention of the condition. Mild cognitive impairment (MCI) is a high-risk potential conversion state prior to a diagnosis of cognitive disorder, where the person still has the ability to live b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This article corroborates the aforementioned observation through an analysis of spatial layout and visual sharing in a dementia rehabilitation center, as well as simulations of human traffic routes. Furthermore, Li et al [60] introduced walking distance as an environmental variable and suggested an optimal layout form. The case layout employed in this study bears resemblance to the one proposed by Li, which centers around a main care station and incorporates multiple tiered nurse stations for collaborative management in a multi-core radial configuration.…”
Section: Discussionmentioning
confidence: 99%
“…This article corroborates the aforementioned observation through an analysis of spatial layout and visual sharing in a dementia rehabilitation center, as well as simulations of human traffic routes. Furthermore, Li et al [60] introduced walking distance as an environmental variable and suggested an optimal layout form. The case layout employed in this study bears resemblance to the one proposed by Li, which centers around a main care station and incorporates multiple tiered nurse stations for collaborative management in a multi-core radial configuration.…”
Section: Discussionmentioning
confidence: 99%